Massive Ascites as the Only Sign of Ovarian Juvenile Granulosa Cell Tumor in an Adolescent: A Case Report and a Review of the Literature - Azin Ashnagar; Samin Alavi; Yalda Nilipour; Roxana Azma; Farahnaz Falahati (Case Reports in Oncological Medicine)
Ovarian neoplasms are relatively rare in childhood and adolescence; only 5% to 8% of the cases are of sex cord stromal origin. Granulosa cell tumors are a group of estrogen producing sex cord stromal tumors of the ovary. They occur in 95% of the cases in adults, and only about 5% of the cases, which differ in histologic characteristics, are of juvenile type. A 13-year-old girl is reported who presented with massive abdominal distention and ascites. An abdominopelvic computed tomography scan showed a predominantly cystic mass lesion with septations arising from the left ovary. All tumor markers were normal, but serum inhibin level was increased. The patient underwent mass resection with salpingoophorectomy. Histopathology was compatible with the juvenile granulosa cell tumor. Interestingly, menarche was started in the patient soon after the surgery. To the best of our knowledge, massive ascites as the only clinical manifestation in the juvenile granulosa cell tumor has not reported as yet.